STUDY OF THE AMINO ACID COMPOSITION OF POULTRY COMBS AS A NON- TRADITIONAL FOOD RAW MATERIAL - Patsera, N. (Жәңгір хан атындағы БҚАТУ, 2023)
The article deals with the possibility and expediency of using poultry combs as a food raw material. Literature data on the world practice of food production from the said raw material are given. A technological chart for the processing of poultry combs at poultry processing enterprises is proposed. The necessary details of the study of the amino acid composition of poultry combs are adduced and the results obtained are presented. The acceptability of the amino acid composition of the said raw material in terms of nutrient adequacy is concluded. В статье рассматривается возможность и целесообразность использования гребней птицы в качестве пищевого сырья. Приведены литературные данные о мировой практике производства пищевых продуктов из указанного сырья. Предложена технологическая схема переработки гребней птицы в условиях птицеперерабатывающих предприятий. Описаны необходимые подробности исследования аминокислотного состава гребней птицы и представлены полученные результаты. Сделан вывод о приемлемости аминокислотного состава указанного сырья с точки зрения нутриентной адекватности.
«ҒЫЛЫМҒА ЖОЛ – 2023» білім алушыларға арналған халықаралық ғылыми-тәжірибелік конференциясының МАТЕРИАЛДАР ЖИНАҒЫ
СБОРНИК МАТЕРИАЛОВ Международной научно-практической конференции обучающихся «ПУТЬ В НАУКУ – 2023»
36 P32 Patsera, N. STUDY OF THE AMINO ACID COMPOSITION OF POULTRY COMBS AS A NON- TRADITIONAL FOOD RAW MATERIAL / N. Patsera, S. Verbytskyi, науч. рук. - Текст : непосредственный // Ғылымға жол-2023: білім алушыларға арналған халықаралық ғылыми-тәжірибелік конф. мат. жинағы (12 суәір 2023 ж.). = Путь в науку-2023: сб. мат. междунар. науч.-практ. конф. обучающихся (12 апреля 2023 г.). = THE PATH TO SCIENCE – 2023: collected papers of the International Scientific-Practical Conference of students (12th of April, 2023). - Орал: Жәңгір хан атындағы БҚАТУ. - 2023. - Т. І. - Б. 190-194 (Орал)
Keywords: отечественное издание; ЗКАТУ; конференции; гребни птицы; переработки гребней птицы; poultry processing industry; poultry by-products; poultry combs; amino acid composition; nutrient adequacy